Reproducibility of Fibrinolytic Response to Venous Occlusion in Healthy Subjects - Stegnar, Mojca; Mavri, Alenka (Thrombosis and Haemostasis, 1995)
Fibrinolytic response to venous occlusion is used to assess the efficiency of the fibrinolytic system. Reproducibility of fibrinolytic variables after 20 min upper arm venous occlusion was investigated in 40 apparently healthy subjects tested twice in a period of 11-23 (mean 15) days. Resting and post-venous occlusion euglobulin clot lysis time, tissue-type plasminogen activator (t-PA) activity, t-PA antigen, plasminogen activator inhibitor (PAI) activity and plasminogen activator inhibitor type 1 (PAI-1) antigen determined on the two occasions did not differ significantly. Positive correlation coefficients for variables before (r=0.43-0.74, all p<0.01) and after venous occlusion (r=0.07-0.66) indicated low to moderate associations between repeated measurements. Differences between repeated measurements relative to the initial measurement were greater after venous occlusion than before venous occlusion and were for euglobulin activity 41 (0-826)%, t-PA activity 27 (2-398)%, and for t-PA antigen 27 (0-179)% (medians and ranges). Poor responses were defined by the lowest (euglobulin activity, t-PA activity and t-PA antigen) or the highest (PAI activity) fifth percentile of the distribution. Almost no agreement between poor responses was observed: poor responses at the first occasion were not determined in the same subjects when re-examined after two weeks. It was concluded that due to relatively low reproducibility of the variables measured after venous occlusion the test needs improvement in order to be potentially clinically useful.